2016
DOI: 10.1111/jpn.12517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Piper sarmentosum extract on the growth performance, antioxidant capability and immune response in weaned piglets

Abstract: The biological properties of Piper sarmentosum render it a potential substitute for antibiotics in livestock feed. This study evaluated the effects of P. sarmentosum extract (PSE) on the growth performance, antioxidant capability and immune response of weaned piglets. Eighty 21-d-old weaned piglets were selected and randomly allocated to one of four dietary treatments with five replicates of four pigs each. The dietary treatments consisted of a basal diet supplemented with 0 (T0), 50 (T50), 100 (T100) or 200 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…The ADG was higher, and F/G was lower in goats fed with the addition of PSE at 300 mg/kg ( p < .05) compared with goats fed with no addition of PSE. The results showed that the higher addition of PSE in the diet was not always associated with a higher feed intake and the lower F/G, similar to the finding of Wang et al (), where piglets supplemented with 50 mg/kg PSE had the highest ADG and feed intake, though this was possibly due to the flavour and palatability of PSE. The beneficial effects of PSE on goat growth performance may be attributed to its anti‐inflammatory activities.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The ADG was higher, and F/G was lower in goats fed with the addition of PSE at 300 mg/kg ( p < .05) compared with goats fed with no addition of PSE. The results showed that the higher addition of PSE in the diet was not always associated with a higher feed intake and the lower F/G, similar to the finding of Wang et al (), where piglets supplemented with 50 mg/kg PSE had the highest ADG and feed intake, though this was possibly due to the flavour and palatability of PSE. The beneficial effects of PSE on goat growth performance may be attributed to its anti‐inflammatory activities.…”
Section: Resultssupporting
confidence: 86%
“…Zakaria, Patahuddin, Mohamad, Israf, and Sulaiman () reported that the aqueous extract of P. sarmentosum has anti‐inflammatory activities in a dose‐dependent manner. Wang et al () also found that PSE could reduce the intestinal inflammation of piglets. Reducing intestinal inflammation would improve the absorption of nutrients in the intestines, which could enhance the growth performance in goats.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that such oxidative stress problems can be alleviated by supplementation with herbal plant (e.g. alfalfa saponin and piper sarmentosum) (Shi et al 2014;Wang et al 2016). Sanguinarine may have exerted its anti-oxidative function by impairing the activity of the nicotinamide adenine dinucleotide phosphate (NADPH) enzyme, which is supported by a study by Qin et al (2006), which demonstrated that sanguinarine is an enzyme inhibitor rather than an reactive oxygen species (ROS) scavenger.…”
Section: Discussionmentioning
confidence: 95%